Parascolymia (Scleractinia: Lobophylliidae) in the Central Paratethys Sea (Vienna Basin, Austria) and its possible biogeographic implications. - Markus Reuter (PLoS ONE, 2015)
Palaeobiogeographical and palaeodiversity patterns of scleractinian reef corals are generally biased due to uncertain taxonomy and a loss of taxonomic characters through dissolution and recrystallization of the skeletal aragonite in shallow marine limestones. Herein, we describe a fossil lobophylliid coral in mouldic preservation from the early middle Miocene Leitha Limestone of the Central Paratethys Sea (Vienna Basin, Austria). By using grey-scale image inversion and silicone rubber casts for the visualization of the original skeletal anatomy and the detection of distinct micromorphological characters (i.e. shape of septal teeth, granulation of septocostae) Parascolymia bracherti has been identified as a new species in spite of the dissolved skeleton. In the recent era, Parascolymia like all Lobophylliidae is restricted to the Indo-Pacific region, where it is represented by a single species. The new species proves the genus also in the Miocene Mediterranean reef coral province. A review of the spatio-temporal relationships of fossil corals related to Parascolymia indicates that the genus was probably rooted in the Eastern Atlantic‒Western Tethys region during the Paleocene to Eocene and reached the Indo-Pacific region not before the Oligocene. The revealed palaeobiogeographical pattern shows an obvious congruence with that of Acropora and tridacnine bivalves reflecting a gradual equatorwards retreat of the marine biodiversity center parallel to the Cenozoic climate deterioration.